TRAINING METHODOLOGY AIMED AT DEVELOPING SPEED QUALITIES IN ATHLETES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The development of speed is a crucial component of athletic performance across a wide range of sports disciplines. As one of the most essential physical qualities, speed significantly contributes to competitive success in sports that require rapid movement, explosive acceleration, and high-intensity efforts over short durations. This paper explores the training methodology specifically designed to enhance speed qualities in athletes, with a focus on both the physiological and biomechanical foundations of speed development. The study analyzes various types of speed, including reaction speed, maximum running speed, acceleration, and speed endurance, and examines how each can be targeted through specific training interventions.The effectiveness of different training methods—such as sprint drills, resisted sprints, plyometrics, neuromuscular activation exercises, and high-intensity interval training—is discussed in detail. Emphasis is placed on training periodization, progressive overload, motor control enhancement, and the integration of sport-specific movement patterns. The role of warm-up routines, recovery strategies, and individualized training programs is also addressed to ensure optimal adaptation and injury prevention. Empirical evidence from sports science literature and practical case studies supports the conclusion that speed development requires a combination of mechanical efficiency, neuromuscular coordination, and anaerobic power. Moreover, the implementation of modern technologies, such as timing gates, video analysis, and wearable motion sensors, allows for more precise monitoring and evaluation of speed training progress. This paper concludes that a systematic, evidence-based, and athlete-centered approach to speed training can lead to significant improvements in performance, particularly when programs are tailored to the athlete’s sport, level of development, and physiological characteristics.